Pseudosarcomatous myofibroblastic lesion of the urinary bladder: A rare entity posing a diagnostic challenge and therapeutic dilemma - Deliveliotis Charalambos; Chrisofos Michail; Mennonna Maria; Papatsoris Athanasios G; Papathomas Thomas G; Parasi Aikaterini; Lekas Alexandros; Lazaris Andreas C (BMC, 2008)
Abstract Background Pseudosarcomatous myofibroblastic lesions of the urinary bladder are relatively rare entities of an uncertain pathogenesis and benign indolent nature. Case presentation We present an extremely rare case of an ALK-1-positive pseudosarcomatous myofibroblastic lesion of the urinary bladder, which was initially misinterpreted as a low-grade leiomyosarcoma of myxoid subtype on histologic examination owing to prominent atypia, high mitotic activity, abnormal mitotic figures and infiltration of the bladder wall. Although the histologic features were suggestive of a sarcoma, the correct diagnosis was finally established and radical surgical treatment was subsequently avoided. The patient is currently free of disease without any evidence of tumor recurrence or metastasis at 3 years post-operatively. Conclusion The key differentiating point rests in distinguishing the aforementioned mass forming lesion from the myxoid subtype of low-grade leiomyosarcoma in order to avoid unnecessary radical therapy.